2013
DOI: 10.1093/nar/gkt1110
|View full text |Cite
|
Sign up to set email alerts
|

Gramene 2013: comparative plant genomics resources

Abstract: Gramene (http://www.gramene.org) is a curated online resource for comparative functional genomics in crops and model plant species, currently hosting 27 fully and 10 partially sequenced reference genomes in its build number 38. Its strength derives from the application of a phylogenetic framework for genome comparison and the use of ontologies to integrate structural and functional annotation data. Whole-genome alignments complemented by phylogenetic gene family trees help infer syntenic and orthologous relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
134
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 42 publications
1
134
1
Order By: Relevance
“…The pipeline was run on the MAKER-P 136 annotations for ten Oryza species and L. perrieri (Table 1). Also included were annotations of three outgroup species, Arabidopsis thaliana (version TAIR10) 137 , Sorghum bicolor (version Sbi1.4) 138 and B. distachyon (version Brachy1.2) 139 , loaded from Gramene v40 Ensembl core databases 140 . Tree reconciliation to classify duplication and speciation nodes, and the assignment of taxon levels to nodes, made use of the following input species tree, which was devised on the basis of results described here (Fig.…”
Section: Ltr-retrotransposon Deletion Ratementioning
confidence: 99%
See 2 more Smart Citations
“…The pipeline was run on the MAKER-P 136 annotations for ten Oryza species and L. perrieri (Table 1). Also included were annotations of three outgroup species, Arabidopsis thaliana (version TAIR10) 137 , Sorghum bicolor (version Sbi1.4) 138 and B. distachyon (version Brachy1.2) 139 , loaded from Gramene v40 Ensembl core databases 140 . Tree reconciliation to classify duplication and speciation nodes, and the assignment of taxon levels to nodes, made use of the following input species tree, which was devised on the basis of results described here (Fig.…”
Section: Ltr-retrotransposon Deletion Ratementioning
confidence: 99%
“…Putative falsely split gene models were detected by an automated pipeline that identifies adjacent 'paralogs' that do not overlap in multiple-sequence alignments 140 .…”
Section: Ltr-retrotransposon Deletion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Only genes with a 100% match to the same chromosome from the v2.1 genome assembly were used for the SNP comparison. EMS-induced SNPs were compared with two natural variation sets available from the Gramene database (Monaco et al, 2014): The first population consists of 265,000 SNPs from 971 worldwide accessions, assayed by genotyping-by-sequencing (Morris et al, 2013); the second population consists of six million SNPs, assayed by whole-genome sequencing of 45 S. bicolor and two S. propinquum lines (Mace et al, 2013). The coordination of SNPs within the mapped genes was converted from the v1.4 assembly to v2.1 using a script written in house.…”
Section: Characterization Of Sorghum Ems-induced Snpsmentioning
confidence: 99%
“…The use of resistance (R) genes is an effective way to control it. Extensive studies have identified more than 90 R genes for resistance to M. oryzae from diverse genetic resources 2 . Most of them are race specific, and all of those genes for race-specific resistance that have been cloned so far encode proteins containing a nucleotidebinding site (NBS) and leucine-rich repeats (LRRs), constituting a major class of R genes in plants 3,4 ; an exception is Pid2, which encodes a receptor-like kinase 5 .…”
mentioning
confidence: 99%